(untitled) (Journal of Pakistan Orthopaedic Association, 2023)
Abstract: Objective: To evaluate clinical and radiological outcomes of individuals undergoing ACDF with or without Uncovertebral joint decompression. Methods: This retrospective study was conducted in Orthopedic and Spine department of Ziauddin University hospital Karachi. Patients meeting inclusion criteria were included. Operative as well as radiological evidence of Uncoforaminotomy was documented. Pre op and Post-Operative VAS score, neck disability index (NDI) and Odom criteria was assessed for neck pain and arm pain immediately, at 2 weeks, 6 weeks and 3 months post op Results: There were 48(68.6%) females and 22(31.4%) male patients. Majority of our patients were in 40-60 years’ age group (34, 48.6%). Most common level involved was C6-7 (48, 68.6%) followed by C5-6 (19, 27.1%). Uncoforaminotomy was performed in 61 (87.1%) of cases. There was significant improvement in NDI and VAS score in 61 (87.1%) cases. Excellent outcome was achieved in 64 (91.4%) of cases as per modified Odom criteria. Significant correlation was found in patients without UF and higher VAS score post op (p-0.001). No significant correlation was found between higher Neck disability index (p-0.075) and presence of Uncoforaminotomy. Subsidence rate was comparable between two groups. No significant correlation was found between Gender and higher post op VAS score (p-0.617). Conclusion: Uncoforaminotomy in ACDF with cervical radiculopathy offers direct decompression of nerve root. Using larger cage in ACDF leads to over distraction of facet joint resulting in stretching of facet capsule and neck pain and higher VAS scores post operatively. Proper knowledge of anatomy of Uncovertebral joint and availability of armamentarium to decompress foramen directly yields excellent outcomes along with minimizing risk of complications. Keywords: Degenerative disc, ACDF, Neck disability score